2009
DOI: 10.1002/jnr.22213
|View full text |Cite
|
Sign up to set email alerts
|

KATP channel openers protect mesencephalic neurons against MPP+‐induced cytotoxicity via inhibition of ROS production

Abstract: Opening of ATP-sensitive potassium (K(ATP)) channels has been demonstrated to exert significant neuroprotection in in vivo and in vitro models of Parkinson's disease (PD), but the exact mechanism remains unclear. In the present study, various K(ATP) channel openers (KCOs) sensitive to diverse K(ATP) subunits were used to clarify the protective role of K(ATP) channel opening in 1-methyl-4-phenylpyridinium (MPP(+))-induced oxidative stress injury in mouse primary cultured mesencephalic neurons. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…It has also been demonstrated that activation of potassium K ATP channels mediate protection in cortical and dopaminergic neurons. 34, 35 Interestingly, activation of mitochondrial calcium-induced calcium release 36 depends on the rate at which Ca 2+ is provided to mitochondria. 37 On the other hand, Ca 2+ accumulation in mitochondria via the uniporter is dependent on the external Ca 2+ concentration and the transmembrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that activation of potassium K ATP channels mediate protection in cortical and dopaminergic neurons. 34, 35 Interestingly, activation of mitochondrial calcium-induced calcium release 36 depends on the rate at which Ca 2+ is provided to mitochondria. 37 On the other hand, Ca 2+ accumulation in mitochondria via the uniporter is dependent on the external Ca 2+ concentration and the transmembrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the highly activated K + channel is a protective mechanism against ischemia/hypoxic stress-induced intracellular Ca 2+ overloading495051. Activation of other K + channels also contributes to the stably maintained and resistant Δψm against cell-death stimuli5253.…”
Section: Discussionmentioning
confidence: 99%
“…While there are numerous examples of neuroprotection by either activation or overexpression of UCP2 (Paradis et al, 2003), the mechanism of protection by uncoupling and inhibition of mitochondrial superoxide production is not uniformly accepted (Cannon et al, 2006). The same lack of consensus applies to the mild uncoupling mechanism by which activators of the mitochondrial ATP-regulated potassium channel, e.g., diazoxide, provide neuroprotection (Xie et al, 2010).…”
Section: Protection Against Mitochondrial Oxidative Stressmentioning
confidence: 99%